Cardiac magnetic resonance findings in neuronal ceroid lipofuscinosis: A case report - Todiere, Giancarlo; Della Vecchia, Stefania; Morales, Maria Aurora; Barison, Andrea; Ricca, Ivana; Tessa, Alessandra; Colombi, Elisa; Santorelli, Filippo Maria (Frontiers in Neurology, 2022)
Cardiac magnetic resonance imaging (MRI) is an essential tool for the study of hypertrophic cardiomyopathies (HCM) and for differentiating HCM from conditions with increased ventricular wall thickness, such as cardiac storage diseases. Although cardiac MRI is already used for the diagnosis and characterization of some forms of storage diseases involving the myocardium, it has not yet been used to study myocardial involvement in neuronal ceroid lipofuscinosis (NCL). Here, we describe comprehensive cardiac MRI findings in a patient with the CLN3 form of NCL showing basal inferior interventricular septal hypertrophy with maintained indexed LV mass within reference values and low T1-native values. MRI findings support a finding of abnormal storage material within the myocardium in CLN3 disease. We recommend the possible routine use of cardiac MRI for early diagnosis of cardiac involvement in CLN3 disease (also termed juvenile NCL) and to monitor the effects of emerging CLN3 therapies on the myocardium as well.